Answer:
Y = 2/3x-8/3
Step-by-step explanation:
y − 4 = 2/3 ( x − 3)
y − 4 = 2/3x -2
y = 2/3x +2
~~~~~~~~~~~~~~~~~
-2 = 2/3(1) + b
b = -2 2/3 = -8/3
Answer:
ez
Step-by-step explanation:
start at the point you were given, and use the slope. remember rise over run.
Answer:
(
)
Step-by-step explanation:
The fastest way to do this is to convert both equations into slope-intercept form and graph it to find the solution point. If you wanted to do this algebraically, you might want to start out by getting rid of the fractions and using either substitution or elimination to find x and y.